Empowerment and Student-Centered: How to Improve the Psychological Resilience of Higher Vocational Students? (Global Journal of Human-Social Science, 2024)
How to improve the psychological resilience of higher vocational students in china has become a theoretical and practical issue that higher vocational colleges urgently need to answer. This article reiterates the "student-centered" concept, integrates the "empowerment" construct research framework, and tentatively interprets the practical situation of improving the psychological resilience of higher vocational students. On the one hand, we create a positive environment through six levels: individual, dormitory, class, family, department, and school. We implement a student-oriented approach and emphasize the importance of fostering external protective factors for psychological resilience. On the other hand, out of the three levels of empowerment, which are empowerment, self-efficacy improvement, and consolidation of the individual's inner self, we practice the concept of empowerment and focus on stimulating the internal protective factors of psychological resilience.
Keywords: psychological resilience; empowerment; student-centered; vocational student